The complete chloroplast genome of Actinidia latifolia, a species with high vitamin C content in fruit. Issue 3 (2nd July 2020) - Qi, Xiaoqiong; Xie, Xiaodong; Zhong, Caihong; Li, Dawei
Abstract: Actinidia latifolia, known for its high vitamin C content in fruits, is widely distributed in the subtropical and tropical regions of eastern and southern Asia. In this study, we sequenced the complete chloroplast (cp) genome sequence of A . latifolia to investigate its phylogenetic position in the gunus Actinidia . The complete cp genome sequence is 156, 873 bp in length with 37.15% overall GC content and characterized by a typical quadripartite structure comprising one pair of inverted repeats (23, 377 bp) separated by a small single-copy region (21, 453 bp) and a large single-copy region (88, 666 bp). The cp genome contains 132 unique genes, including 83 protein coding genes, 41 tRNA genes, and 8 rRNA genes. Phylogenetic analysis highly supported that A. latifolia evolutionarily close to A. eriantha .